EFFECTS OF INFORMATION TECHNOLOGY ON BANKING SERVICE - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The banking sector should anticipate challenges when adopting the use of technology so as to increase the possibility of success when using different forms of technology. Bradley and Stewart (2003), note that in the 21st century, many of the world banks use some form of technology. The research also found out that small banks have reaped great benefits from the emergence and use of technology. This conclusion is echoed by Vainio (2006) who concludes that the use of technology to provide services by small banks help them to gain a competitive advantage.Poon (2008) notes that security and privacy in technological banking are the main source of dissatisfaction among banking customers and thus the influence the satisfaction of customers.However, advantages of technological banking that has yielded satisfaction from customers include better content provision of banking services, convenience, design and easier accessibility. E-banking success can also be affected by the banks speed in offering e banking services, the operational management of the e-banking services, the cost of using e banking for the customer and product features on the e-banking platform